PENGEMBANGAN MEDIA PEMBELAJARAN POSTER BERBASIS PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII MTs NW SUKAMULIA PADA MATERI SISTEM PENCERNAAN MANUSIA - Ariandani, Nunung (Cocos Bio, 2025)
This study aims to: (1) Develop Problem-Based Learning (PBL)-based Poster Learning Media to Improve Student Learning Outcomes, (2) Determine the feasibility and validity of Problem-Based Learning (PBL)-based Poster Learning Media to Improve Student Learning Outcomes, (3) To determine the effectiveness of Poster-Based Learning Media Using Problem-Based Learning (PBL) in Improving Student Learning Outcomes. This development study employs the 4D model, which consists of four stages: Define, Design, Development, and Dissemination. The subjects of this study were subject matter experts, media experts, science teachers, and 20 students from MTs NW Sukamulia. Data collection techniques used questionnaires and tests that had previously undergone validity tests, reliability tests, difficulty level tests, and discrimination power tests. Based on the data analysis and discussion, the product is deemed suitable and valid for use in teaching and learning activities. This suitability is evident from the average suitability scores obtained: subject matter experts 3.6, media experts 3.6, science teachers 3.2, and student responses 3.6. These scores meet the criteria for good and very good. Furthermore, the validity of the poster learning media can be seen from the percentage of ideality from subject matter experts (90%), media experts (91%), science teachers (79%), and student responses (90%). Based on the percentage of ideality, the results obtained meet the criteria for valid and highly valid. Based on the average percentage for improving student learning outcomes, it falls into the very good category.